1998
DOI: 10.1046/j.1365-2370.1998.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor β gene polymorphisms in myasthenia gravis

Abstract: Genetic analyses indicate that genes within the major histocompatibility complex (MHC) can be involved in susceptibility to autoimmune disease. To investigate the role of the tumour necrosis factor beta (TNFB) gene in myasthenia gravis (MG) susceptibility, we analysed an NcoI polymorphism within the TNFB gene in 63 MG patients and 93 healthy individuals. When patients were subdivided according to thymic pathology, we found differences between MG patients with thymic hyperplasia and thymoma versus controls. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The genetics of the autoimmune response in MG are not well understood, although associations with HLA, tumor necrosis factor, and T-cell receptor V␤ have been reported [5,20,21]. However, one important feature in MG is the consistent association with different HLA antigens in populations with different ethnic background [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetics of the autoimmune response in MG are not well understood, although associations with HLA, tumor necrosis factor, and T-cell receptor V␤ have been reported [5,20,21]. However, one important feature in MG is the consistent association with different HLA antigens in populations with different ethnic background [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Immunogenetic studies in healthy and diseased populations have demonstrated that several genes besides major histocompatibility complex (MHC) genes play an important role in determining an individual's susceptibility to the development of MG [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly the higher frequency of allele-G of TNF-β (+252) polymorphisms in patients (P=0.011) indicated that Allele G is associated with glaucoma. TNF-β (+252) polymorphism has earlier been reported to be associated with a number of autoimmune diseases (Albuquerque et al, 1998;Zelano et al, 1998;Pandey et al, 1999;Vasku et al, 2000;Kula et al, 2001;Lu et al, 2005;Takeuchi et al, 2005;Panoulas et al, 2008;Boraska et al, 2009;Watanabe et al, 2010;Tiancha et al, 2011) however, this is the first report on the association between TNF-β polymorphism and glaucoma. The presence of allele G at +252 position defines the mutant allele also known as TNF-β* 1 (allele-1) is reported to be associated with higher TNF-α and TNF-β production (Messer et al, 1991;Abraham et al, 1993).…”
Section: Studymentioning
confidence: 83%
“…The presence of G at this position defines the mutant allele known as TNF-β * 1 (allele-1) which is less frequent allele in white subjects and is associated with higher TNF-α and TNF-β production (Messer et al, 1991;Abraham et al, 1993). Association of TNF-β +252 A/G polymorphism has been reported with various autoimmune disorders including Gravis' disease (Kula et al, 2001) idiopathic membranous glomerulonephritis, IgA nephropathy, insulin dependent diabetes mellitus (Medcraft et al, 1993) , myasthenia gravis (Zelano et al, 1998), asthma diathesis (Albuquerque et al, 1998), SLE with nephritis (Lu et al, 2005), systemic sclerosis (Pandey &Takeuchi, 1999), plaque psoriasis (Vasku et al, 2000), rheumatoid arthritis (Takeuchi et al, 2005), myocardial infarction in patients with rheumatoid arthritis (Panoulas et al, 2008), and type 1 diabetes (Boraska et al, 2009). Recently TNF-β +252 A/G polymorphism is reported to be associated with both susceptibility to and mortality from sepsis (Watanabe et al, 2010;Tiancha et al, 2011).…”
mentioning
confidence: 99%
“…TNF-β has also been shown to contribute to the susceptibility of several inflammatory/autoimmune diseases. Association of TNF-β +252 A/G polymorphism has been reported with various autoimmune disorders including Gravis' disease [47] idiopathic membranous glomerulonephritis, IgA nephropathy, insulin-dependent diabetes mellitus [48], myasthenia gravis [49], asthma diathesis [50], SLE with nephritis [51], systemic sclerosis [52], plaque psoriasis [53], rheumatoid arthritis [54], and type 1 diabetes [55]. Recently, TNF-β +252 A/G polymorphism is reported to be associated with both susceptibility to and mortality from sepsis [56].…”
Section: Introductionmentioning
confidence: 99%